After mining catastrophe: the language of economic survival of the Sipalay mine people at Sipalay, Negros Occidental, Philippines - Barrientos, Rubie Lyn C.; Pilar, John Gerald A. (Brawijaya University, 2026)
The mining industry has intimate ties to the environment, economy, and society. Its life cycle impacts communities in both positive and negative ways, affecting the community. This research investigated the experiences of miners from the Sipalay Mine, which was owned by Maricalum Mining Corporation, formerly Marinduque Mining Industrial Corporation. Using a qualitative approach and ethical research standards, ten purposively selected informants shared their stories. The informants demonstrated resilience by adjusting to challenging situations, striving for a better life, implementing mitigation strategies, and finding contentment in their current circumstances. Following the closure of the mine, former miners faced unemployment and limited resources, but they positively turned to self-determination, exploiting their resource management and entrepreneurial talents. This study proposed the ENCOMTRACOM (Engagement Community, Transitioning Community) collaborative model to ensure sustainable development. This model promotes community involvement, fosters economic growth through livelihood projects, encourages stakeholder collaboration, and facilitates effective communication. Moreover, three layers of scaffolding frameworks: (1) the challenges miners faced post-closure, including unemployment and resource scarcity; (2) the miners’ strengths in resource management, entrepreneurship, and training; and (3) their ability to build resilience through community support, safer livelihoods, and skill development. Overall, the Sipalay miners have demonstrated their adaptability by striving for improvement, reducing risks, and finding fulfillment. This research advocates for the development of future programs on community assistance, entrepreneurship training, and collaboration among universities, local government, and NGOs. While this study may be limited for researchers, this research provides valuable insights for future initiatives on sustainable recovery in post-mining communities.